(untitled) (European Bison Conservation Newsletter, 2013)
The three years experiences of implementing the conservation program of European bison in Spain are presented. First import was from Poland in year 2010 (7 animals) and second from Lelystad in the Netherlands (17 animals). Those animals were transferred to 4 enclosures of different size and condition. The stories about all four enclosures are presented.